Stock Market And Economic Growth In Libya - Amna Khalifa Salem Edweib; Zurina Shafii; Nursilah Ahmad (International Organization of Scientific Research (IOSR), 2024)
The study aims to examine the role of the Libyan Stock Market (LSM) in Libyan economic growth from the perspective of brokers, employees and investors. A set of questionnaire are employed to identify the role of stock market in promoting economic growth, the problems inherent to LSM and the measures taken by the market to improve its contribution in economic growth. The findings indicate that the brokers, employees and investors agreed that LSM has significant potential to positively contribute to Libya's economic growth. The findings imply that in order to improve contribution of LSM in economic growth, the Libyan stock market authority need to improve their policies to encourage more companies, especially main sectors companies such as oil, energy, and telecommunication, to contribute in the market. A set of regulations is also needed to develop LSM culture and to attract the local and foreign investors.